A metaphorical study on teaching individual creativity in Asia: Indian Alap and Vietnamese Dao - Jahnichen, Gisa; Meddegoda, Chinthaka Prageeth (Center for Promoting Ideas, 2014)
Societies and cultures in Asia are everywhere strongly reflected through ways and strategies of transmitting performing arts such as music and dance. In this study, we take the transmission of some essentials in music tradition from two different places in Asia, namely India and Vietnam, as a metaphor to be further applied on cultural and social analysis in order to achieve a better understanding of how creativity is taught and culturally established. Indian music is asserted as a Gurumukhi Vidya (Guru centered science) in musical treatises found in India. In the learning process, both Guru and disciple continue their duties for each other which are very necessary to construct a suitable cognitive environment within both sender and receiver. The process of transmitting knowledge might be successful as far as the teacher gains satisfaction and a real impression on the student and at the same time by the student’s behavior and capability of receiving and applying knowledge. Similar yet different processes can be observed with teaching in the Vietnamese music tradition. Ālāpis a very important part in north Indian classical music as well as the Dạo in the Vietnamese music tradition as they dominantly create the mood of a Rāga or a Ðiệu1 respectively in an improvisatory manner that demands a high input of individual creativity. Teachers usually initiate teaching after providing a brief introduction of basic elements. It is essential that students should follow first every phrase in a parallel way as the teacher articulates. This process is continued until the students understand the approximate picture of the Rāga or Ðiệu. Subsequently the teacher allows the student to improvise in his own way by keeping to the rules thus a student develops creativity through developing individuality. The final outcome is then an improvisation. Nevertheless, some contradictions in transmission and perception can be stated such as between the supposedly “free” in an improvisation and the strict way of teaching the “free”. So, individuality and creativity develop in a process of tension between rules and breaking rules. Metaphorically, we can see strong parallels to other subjects of transmitting social and cultural patterns of communication that are perceived differently from the perspective of the West and East. In discovering cultural individuality in dealing with creativity, social developments can be seen much clearer and concepts of creative developments could be more effectively reasoned within the societies concerned. Though this study cannot be comprehensive in direct application of musicological findings on social behavior, it may help to open up new interdisciplinary ways in conducting social analysis, mainly to provide a methodological path in recognizing possible stimuli for future creativity in different Asian societies.